The framing and governance of climate change adaptation projects in Lao PDR and Cambodia - Louis Lebel (2018)
© 2018 Springer Science+Business Media B.V., part of Springer Nature This study explores the way climate change adaptation projects in Cambodia and Lao PDR have been framed. Four frames were identified: inadequate infrastructure; information deficits; limited planning capacity; and insecure access. In all frames, there was internal coherence among: the problems identified; the form solutions are expected to take; and who should be included and in what roles. All projects claimed to be addressing the needs of farmers vulnerable to climate change. The infrastructure, information, and capacity frames are apolitical and privilege expert knowledge, whereas the access frame places rights and justice issues centrally, and thus holds more potential for addressing the root causes of vulnerabilities and supporting more just distribution of resources and power. Framing can interact with how projects are governed, for example, through assigning roles to actors based on types of solutions prescribed. The extent and direction of frame elaboration also depend on how a project is governed. Meeting local needs and objectives, for example, is constrained when external actors have too much influence in project governing structures, and initial project plans written from afar are followed too narrowly. This study shows that frames are an important part of the governance of adaptation projects.